2022
DOI: 10.3390/curroncol29080423
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Basal Cell Carcinoma with Electrochemotherapy: Insights from the InspECT Registry (2008–2019)

Abstract: This prospective registry-based study aims to describe electrochemotherapy (ECT) modalities in basal cell carcinoma (BCC) patients and evaluate its efficacy, safety, and predictive factors. The International Network for Sharing Practices of Electrochemotherapy (InspECT) multicentre database was queried for BCC cases treated with bleomycin-ECT between 2008 and 2019 (n = 330 patients from seven countries, with 623 BCCs [median number: 1/patient; range: 1–7; size: 13 mm, range: 5–350; 85% were primary, and 80% lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…Specifically, the outcome data for melanoma (CR 85.6%) are at least comparable to data published by Kunte et al who demonstrated an OR of 78% and a CR of 58% [12]. Similarly, CR in the BCC cohort (83.3%) was equivocal to previous studies which showed response rates of 72.5% [15], 81% after a single treatment [26], further demonstrating the efficacy of HF-EP across different histiotypes.…”
Section: Discussionsupporting
confidence: 78%
“…Specifically, the outcome data for melanoma (CR 85.6%) are at least comparable to data published by Kunte et al who demonstrated an OR of 78% and a CR of 58% [12]. Similarly, CR in the BCC cohort (83.3%) was equivocal to previous studies which showed response rates of 72.5% [15], 81% after a single treatment [26], further demonstrating the efficacy of HF-EP across different histiotypes.…”
Section: Discussionsupporting
confidence: 78%
“…Still, it is impossible to make general considerations because there are only sporadic studies, mainly focusing on single approaches [ 256 , 257 , 258 , 259 ], and a lack of comparative analyses. Finally, the best available evidence for PEF-based therapies is still heterogeneous, ranging from prospective randomised trials [ 16 , 112 , 230 , 260 ] and large registry-based studies [ 153 , 158 , 200 ] to small case series or case reports. In addition, these therapies have a vast range of applications and are primarily used in combination or as part of sequential multimodal strategies, thus making it challenging to conduct informative comparative trials.…”
Section: Discussionmentioning
confidence: 99%
“…Despite no convincing evidence compared with standard surgical excision, ECT can still be considered an opportunity to avoid the morbidity of surgical resection in selected patients. To this aim, treatment naïvety, no previous radiation, and the ability to cover tumour margins may inform patient choice [ 158 ].…”
Section: Electrochemotherapymentioning
confidence: 99%
“…Nos últimos 20 anos, a eletroquimioterapia tem sido aplicada principalmente em um ambiente paliativo, permitindo o controle de sangramentos e sintomas relacionados à massa. (Peris et al, 2023) As indicações de eletroquimioterapia propostas no estudo podem ser resumidas da seguinte forma: tratamento de CBC de baixo risco em subgrupos estritamente selecionados, impróprios para tratamento cirúrgico por causa de sua idade ou comorbidades; tratamento de preservação de órgãos de CBC de pequeno porte de alto risco localizado em áreas anatômicas delicadas, como na pálpebra, nariz e aurícula em pacientes que não estão aptos ou se encontram dispostos a preservar o funcionamento do paciente; tratamento auxiliar de CBC localmente avançado em conjunto com o tratamento sistêmico (Bertino et al, 2022).…”
Section: Materiais E Métodosunclassified